Getting at the Variable Expressivity of Von Willebrand Disease - Levy, Gallia; Ginsburg, David (Thrombosis and Haemostasis, 2001)
Von Willebrand disease (VWD) is a heterogeneous bleeding disorder caused by abnormalities of von Willebrand factor (VWF). VWF levels vary widely in the general population, and this variation is likely to be a major factor accounting for the incomplete penetrance and variable expressivity of VWD. In addition, variation in VWF level may play an important role in determining the risk of venous thrombosis. A large component of the variation in VWF level in the general population has been shown to be attributable to genetic factors. This review will focus on the current understanding of the genetic causes for variation in VWF level, and will highlight future directions for getting at the variable expressivity of von Willebrand disease.
Keywords: Von Willebrand factor; von Willebrand disease; variable expressivity; ABO blood group; thrombosis